2022
DOI: 10.3389/fpsyt.2022.809173
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Exposure, Post-traumatic Stress Disorder, Conflict Behaviors, and Online Aggressive Behaviors Among College Students During the COVID-19 Pandemic: Examining the Moderating Role of Gender

Abstract: The COVID-19 pandemic impacts people’s mental health and behaviors, but the influence mechanism between pandemic exposure, conflict behaviors, and online aggressive behaviors during the COVID-19 outbreak remains unclear. This study will address this gap. Data were collected from 1,153 college students in an online survey that included an pandemic experiences scale, a post-traumatic stress disorder (PTSD) scale, a conflict behaviors scale, and an online aggressive behaviors scale. Structural equation modeling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…Similar findings have also been reported in previous studies discussing PTSD symptoms based on gender. Research conducted by Zhen et al (2022) reported different PTSD symptoms experienced by men and women, similar to what we have found in this study. In detail, significant differences were observed in the emotional, mental, behavioral, and spiritual aspects.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have also been reported in previous studies discussing PTSD symptoms based on gender. Research conducted by Zhen et al (2022) reported different PTSD symptoms experienced by men and women, similar to what we have found in this study. In detail, significant differences were observed in the emotional, mental, behavioral, and spiritual aspects.…”
Section: Discussionsupporting
confidence: 90%
“…Neurodevelopmental disorders, such as ADHD, can also play a part in aggressive behavior [16]. In most cases, this behavior is triggered by a particular event, such as a pandemic [34]. Aggressiveness can happen as a natural response to pandemic-related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodevelopmental disorders, such as ADHD, can also play a part in aggressive behavior [16]. In most cases, this behavior is triggered by a particular event, such as a pandemic [34]. Aggressiveness can happen as a The rs6323 variant of MAOA, located in the exonic region, is associated with altered enzyme activity; the G allele is linked to higher levels of the enzyme and the T allele is linked to lower levels [50].…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas chinesas, realizadas no ano de 2020 com estudantes de instituições superiores da China, encontraram, à análise da consistência interna da PCL-5, um Alfa de Cronbach de 0,96 (Yang et al, 2022;Zhen et al, 2022), mesmo número verificado para nossa escala global, corroborando os achados aqui apresentados. Elbarazi (2022), em estudo aplicado com universitários residentes no Egito, obteve um Alfa de 0,93 para a referida escala, quantia esta que se enquadra abaixo das percebidas neste trabalho, mas mantém-se na faixa de valores atribuídos a uma consistência interna de caráter adequado.…”
Section: Item N M Dp Cv Mín-máxunclassified